Imagens e imaginários do campo jurídico nas mídias - Souza, Alexsandrina Ramos de Carvalho (Universidade do Vale do Rio dos Sinos, 2021)
The present thesis aims to know the meanings given to the legal field in the interfaces of various media understanding the imaginaries that cross the images. The legal field is thought of in this research from the bergsoniana intuition (BERGSON, 2005; DELEUZE 2004), presenting itself as a virtual that updates itself in the media. Therefore, the research is crossed by the following problem: How do various visual and audiovisual media give to see the legal field and which imaginaries are called to build these technical and aesthetic worlds of Law? Flânerie (BENJAMIN, 2006) became the methodological path that allowed us to observe with all senses some images of the legal field present in the television worlds (KILPP, 2003), in serial fiction, in television news, but also in websites and applications as well as in images of live communication platforms in times of pandemic. To think about images and imaginaries, authors such as Flusser (1985), Castoriadis (1995) and Maffesoli (2001) were fundamental. Among the conclusions, we understand that the media become one of the most important territories of meaning of the legal worlds.
Keywords: Imagens; Imaginários; Campo jurídico; Mídias; Images; Imaginary; Legal field; Media; ACCNPQ::Ciências Sociais Aplicadas::Comunicação